PARTISIPASI PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN DI TINGKAT DESA: STUDI KASUS PADA BADAN PERWAKILAN DESA SEKECAMATAN BANYUDONO KABUPATEN BOYOLALI - Widayati, Tri (JIV-Jurnal Ilmiah Visi, 2006)
This research aims at (a) finding out the participation of female members of The Board of Village Representatives (BPD) in Banyudono Subdistrict, Boyolali District, in initation, legitimation, exution, and evaluation of the decisions at the village level, (b) discovering internal and external factors in the participation, and (c) formulating some suggestions in developing the programs of empowering the females roles of BPD members. Results indicate very low participation of BPD female members in initation, legitimation, and evaluation but moderately high in the excution of decisions. Although they have high formal education, they lack in nonformal and informal education wich make them weak in attitude. Research suggests that (a) the female members of BPD should improve their knowledge in village government, budgetting, legislation, and supervision; (b) BPD should organise training for all its members; (c) the recruitment criteria for its members should be adjusted to the local society; and further study should be conducted to strengthen the role of female members of BPD.